AVSP - Do infants detect A→V articulator congruency for non-native click consonants? - Best, Catherine T.; Kroos, Christian; Irwin, Julia (2011)
Keywords: dept.psy

Do infants detect A→V articulator congruency for non-native click consonants? - Best, Catherine T; Kroos, Christian; Irwin, Julia (Proceedings of the International Conference on Audio-Visual Speech Processing (AVSP2011), Aug 31 - Sep 3, 2011, Volterra, Italy, 2011)
Keywords: dept.psy; ⛔ No DOI found

Can children with autism spectrum disorders “Hear” a speaking face? - Irwin, Julia; Tornatore, Lauren A; Brancazio, Lawrence; Whalen, D H (Child Development, 2011)
This study used eye-tracking methodology to assess audiovisual speech perception in 26 children ranging in age from 5 to 15 years, half with autism spectrum disorders (ASD) and half with typical development. Given the characteristic reduction in gaze to the faces of others in children with ASD, it was hypothesized that they would show reduced influence of visual information on heard speech. Responses were compared on a set of auditory, visual, and audiovisual speech perception tasks. Even when fixated on the face of the speaker, children with ASD were less visually influenced than typical development controls. This indicates fundamental differences in the processing of audiovisual speech in children with ASD, which may contribute to their language and communication impairments.
Keywords: Adolescent; Child; Child Development Disorders, Pervasive; Child, Preschool; Communication; Female; Humans; Language Development Disorders; Lipreading; Male; Pattern Recognition, Visual; Perceptual Masking; Reference Values; Speech Perception; Verbal Behavior; adolescent; article; autism; child; dept.hls; dept.psy; female; human; interpersonal communication; language disability; lip reading; male; pattern recognition; perception; preschool child; psychological aspect; reference value; speech perception; verbal behavior

Functional activation for imitation of seen and heard speech - Irwin, Julia R.; Frost, Stephen J.; Mencl, W. Einar; Chen, Helen; Fowler, Carol A. (Journal of Neurolinguistics, 2011)
This study examined fMRI activation when perceivers either passively observed or observed and imitated matched or mismatched audiovisual (”McGurk”) speech stimuli. Greater activation was observed in the inferior frontal gyrus (IFG) overall for imitation than for perception of audiovisual speech and for imitation of the McGurk-type mismatched stimuli than matched audiovisual stimuli. This unique activation in the IFG during imitation of incongruent audiovisual speech may reflect activation associated with direct matching of incongruent auditory and visual stimuli or conflict between category responses. This study provides novel data about the underlying neurobiology of imitation and integration of AV speech. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Audiovisual; FMRI; Imitation; McGurk effect; Speech perception; Speech production; adult; article; auditory stimulation; brain function; brain region; controlled study; dept.psy; female; functional magnetic resonance imaging; human; human experiment; inferior frontal gyrus; male; priority journal; speech discrimination; speech perception; superior temporal gyrus; task performance; visual stimulation